PRODUCTION OF STAR FRUIT ROOTSTOCKS FERTILIZED WITH DIFFERENT BORON DOSES - Xavier, Clariana; Natale, William (REVISTA DE AGRICULTURA, 2017)
Among the tropical fruits, star fruit stands out due to its flavor and nutritional properties. Nevertheless, the information on fertilization and nutrition of this fruit is still scarce. For this reason, this study aimed to assess the effect of different boron doses on star fruit rootstock growth. The experimental design was randomized block design, consisting of five treatments of boron application (0, 1, 2, 3, and 4 mg dm−3) and four replications. Star fruit rootstock did not respond to boron doses applied to the substrate and hence it did not influence the parameters stem diameter, plant height, the number of leaves, dry mass of shoot, dry mass of roots, total dry mass, and Dickson quality index (DQI). A boron dose up to 4 mg dm−3 (800% of the recommended boron dose of 0.5 mg dm−3) did not produce symptoms of visual toxicity in the plant.